Neurotype and participatory autism knowledge predict perceptions of an autistic employee in the workplace - Szechy, Kathryn A.; O'Donnell, Lisa A. (Frontiers in Organizational Psychology, 2024)
Autistic adults are unemployed at much higher rates than the general population. Differences from autistic traits, including social skills differences, are often barriers to autistic adults obtaining and retaining employment in non-autistic workplaces. The Double Empathy Problem (DEP) posits that autistic social differences are not due to autistic social impairment but to mutual misunderstandings within the autistic/non-autistic social interaction. Consistent with the DEP, autistic adults are more likely to accurately interpret the behavior of an autistic employee, compared to non-autistic adults.This study examined additional factors, beyond neurotype, that are associated with accurate interpretation of the behavior of an autistic employee. A sample of 73 autistic and 140 non-autistic participants read a vignette about a hypothetical autistic employee in a non-autistic workplace having a difficult workday. Participants completed questions about their interpretation of the employee's behavior, an autism knowledge measure, autism experience questions and demographic information.General autism knowledge, but not autism experience, was an influential predictor of accurate behavior interpretation towards the autistic employee and negated the predictive influence of education level, income, and gender identity of participants (OR = 1.12, p < .001). However, regardless of level of autism knowledge, autistic participants continued to be significantly more likely to accurately interpret the behavior of the autistic employee, compared to non-autistic participants (OR = 2.94, p = .02). Results continue to support the DEP within the context of autistic employment challenges. Findings also point to autism education as a promising autism workplace support in addressing the DEP and barriers autistic adults face with obtaining and retaining employment.